2008
DOI: 10.1080/02841860802001442
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful preoperative biopsies, fine needle aspiration cytology or core needle biopsy, lead to increased costs in the diagnostic workup in breast cancer

Abstract: Correct preoperative diagnosis of a breast lesion is essential for optimal treatment planning. Our aim was to compare feasibility of fine needle aspiration cytology (FNAC) and core needle biopsy (CNB) in diagnosis of breast lesions. The special aim was to evaluate the extra costs and delay in surgical treatment due to unsuccessful preoperative biopsies. Diagnostic work-ups in 572 patients with 580 breast lesions were retrospectively evaluated. FNAC was the first biopsy method for 339 lesions, CNB for 241 lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 19 publications
0
36
0
4
Order By: Relevance
“…CNB is a routinely used method for preoperative assessment of breast cancer patients (1-3,5). CNB may not completely represent the biological profile of the tumor in all cases because of sampling errors (15), insufficient sample size of the CNB, fixation problems of RSs, intratumoral heterogeneity, and menopausal status of patients (3,5,8,9). The aim of this study was to assess the concordance of CNB and RS results and to clarify the reasons for discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…CNB is a routinely used method for preoperative assessment of breast cancer patients (1-3,5). CNB may not completely represent the biological profile of the tumor in all cases because of sampling errors (15), insufficient sample size of the CNB, fixation problems of RSs, intratumoral heterogeneity, and menopausal status of patients (3,5,8,9). The aim of this study was to assess the concordance of CNB and RS results and to clarify the reasons for discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…FNAC has average success rates of 75-90% for palpable and 34-58% for non-palpable breast lesions, whereas success rates reported for CNB are 97% and 94%, respectively (18,21,27). Another important criterion is represented by the lesion size.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…In the case of (potential) malignancy, the speed advantage of FNaC over CNB seems irrelevant in view of the required multidisciplinary meeting to arrive at a therapy plan. an interesting study showed that an indefinite diagnosis using FNaC required additional CNB and surgical excision biopsies in 32% and 21% of cases respectively (31 …”
Section: Cnb and Histopathology Of C3 (Atypia Probably Benign) Categomentioning
confidence: 99%